Using heart rate and ratings of perceived exertion to monitor intensity during a 5 km run in trained runners - Evans, B. W.; Potteiger, J. A. (Medicine & Science in Sports & Exercise, 1995)
The validity of using heart rate, and central and peripheral ratings of perceived exertion (at 4 mM lactate), obtained during a graded treadmill run, for monitoring intensity in a 5 km field run, was examined. Using heart rate to maintain steady state effort levels was related more to performance than either form of perceived exertion. Implication: In steady state endurance events, heart rate levels are related to performance in trained runners more than ratings of perceived exertion.